2009
DOI: 10.1021/am900612r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures of the Buried Interfaces between Silicone Elastomer and Silane Adhesion Promoters Probed by Sum Frequency Generation Vibrational Spectroscopy and Molecular Dynamics Simulations

Abstract: Silane adhesion promoters are commonly used to enhance the adhesion of elastomeric materials to polymers in many industrial applications. However, it is difficult to study the molecular-level mechanisms underlying adhesion promotion because adhesion occurs at the boundary between two layers, a buried interface that is difficult to probe with most techniques. Here, a surface/ interface-sensitive optical technique, sum frequency generation vibrational spectroscopy, was used to probe the buried interfaces between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
0
27
1
Order By: Relevance
“…The peak centered around 3000–3010 cm –1 is assigned to the epoxy C–H stretching of γ-GPS, indicating the presence of the epoxy end group of γ-GPS at the silicone/d4-PET interface with order . The sharp peak at 2840–2845 cm –1 is assigned to the symmetric C–H stretching of the methoxy head group in γ-GPS. , The peaks at 2875 and 2925–2935 cm –1 are assigned to the symmetric and anti-symmetric −CH 2 stretching, respectively, from the backbone methylene groups of DMMVS and γ-GPS as well as the curing agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak centered around 3000–3010 cm –1 is assigned to the epoxy C–H stretching of γ-GPS, indicating the presence of the epoxy end group of γ-GPS at the silicone/d4-PET interface with order . The sharp peak at 2840–2845 cm –1 is assigned to the symmetric C–H stretching of the methoxy head group in γ-GPS. , The peaks at 2875 and 2925–2935 cm –1 are assigned to the symmetric and anti-symmetric −CH 2 stretching, respectively, from the backbone methylene groups of DMMVS and γ-GPS as well as the curing agent.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have carried out systematic studies to reveal the adhesion promotion mechanism of alkoxysilane-siloxane mixtures on aliphatic group-deuterated polyethylene terephthalate (d4-PET) using SFG. , The interfacial ordering of the three methoxy end groups of (3-glycidoxypropyl)­trimethoxysilane (γ-GPS, which is an alkoxysilane, Scheme ) was found to play important roles in determining adhesion strength at the silicone/PET interface. The addition of DMMVS (hydroxyl-terminated dimethyl methylvinyl co-siloxanol, Scheme ) caused more ordering of the methoxy groups at the d4-PET/silicone interface before curing and, therefore, promoted the adhesion by the interfacial chemical reactions between methoxy groups and hydroxyl end groups of PET during the curing process. , …”
Section: Introductionmentioning
confidence: 99%
“…Two different silanes, n -octadecyltrimethoxysilane (OTMS, CH 3 (CH 2 ) 7 Si(OCH 3 ) 3 ) and (tridecafluoro-1,1,2,2-tetrahydroctyl)trimethoxysilane (TDFTMS, CF 3 (CF 2 ) 5 (CH 2 ) 2 Si(OCH 3 ) 3 ), and their mixtures with MVS in contact with cured PDMS have also been examined using SFG. Molecular dynamics simulation was used to confirm SFG results [161]. …”
Section: Polymer-silane Interactionsmentioning
confidence: 99%
“…There is a need to develop an ultrasensitive technique which could be used to study the distribution of ultrathin silicone oil layers on surfaces. In recent decades, second-order nonlinear optical spectroscopic techniques such as sum frequency generation (SFG) vibrational spectroscopy and second-harmonic generation (SHG) have been applied to study molecules (including proteins) on surfaces and at interfaces. Such research demonstrated that second-order nonlinear optical spectroscopic techniques are very promising in detecting monolayer and even submonolayer molecules at interfaces in situ. SFG has been applied to examine the molecular structures of surfaces and interfaces involving solid silicone and silicone oil to understand important interfacial properties such as adhesion, friction, antifouling, and fouling release. In particular, SFG has been applied to study thin films of silicone on water surfaces . SFG provides chemical and orientational information on the molecular structure of chemical groups at interfaces.…”
Section: Introductionmentioning
confidence: 99%